Retirement blues - Heller-Sahlgren, Gabriel (Journal of health economics, 2017)
•This paper analyses the effects of retirement on mental health in Europe.•Regular state pension ages are used for identification purposes.•We find no short-term effects, but a large negative longer-term impact.•There is no evidence of heterogeneous effects across different groups. This paper analyses the short- and longer-term effects of retirement on mental health in ten European countries. It exploits thresholds created by state pension ages in an individual-fixed effects instrumental-variable set-up, borrowing intuitions from the regression-discontinuity design literature, to deal with endogeneity in retirement behaviour. The results display no short-term effects of retirement on mental health, but a large negative longer-term impact. This impact survives a battery of robustness tests, and applies to women and men as well as people of different educational and occupational backgrounds similarly. Overall, the findings suggest that reforms inducing people to postpone retirement are not only important for making pension systems solvent, but with time could also pay a mental health dividend among the elderly and reduce public health care costs.